Abandoning female genital mutilation/cutting information from around the world (Washington, DC : Population Reference Bureau, 2005)
This CD-ROM is a compilation of recent research and analysis from ar ound the world regarding female genital mutilation/cutting. Statistical data, evaluation reports, training manuals, tools, and links to other organizations are presented here with the aim of providing useful infor mation to individuals, organizations, and governments working to elimin ate the practice of FGM/C.
Development of this CD-ROM has been funded by the U.S. Agency for In ternational Development (USAID) under the BRIDGE Project (No.GPO-A-00-0 3-00004-00).
System requirements: Internet Explorer 5.5+, Mozilla 1.0+ or Safari, Adobe Acrobat Reader
English and French
Keywords: Female circumcision -- Prevention